The current use of GPS, its potential, and limitations in soccer - Hennessy, L.; Jeffreys, I. (Strength and Conditioning Journal, 2018)
In soccer, global positioning system (gps) monitoring of player workloads is now extensively used across all levels of the sport. To make better use of this technology it is important to appreciate how it works. Further, when the limitations of gps use are appreciated and the rationale of use is agreed and articulated, then the potential of gps monitoring can be effectively realized to better manage players' performance, workload and welfare. (see video, supplementary digital content, number 1, which summarizes gps use, limitations, and potential in soccer, http://links.lww.com/scj/a238